IMMUNOTHERAPY BASED ON DENDRITIC CELLS IN BLADDER CANCER TREATMENT - A. S. Ilnitskaya; A. B. Danilova; I. A. Baldueva (Успехи молекулярной онкологии, 2018)
The development of an antitumor vaccine based on autologous dendritic cells (DCs) for bladder cancer treatment is extremely relevant today due to the proven high immunological potency of this type of tumor. Vaccination with DCs-based drugs as a monotherapy or in combination with other methods of treatment has shown to be effective in cancer therapy. The vaccine administration is considered to be safe, the associated side effects are insignificant and can be characterized as undesirable phenomena of 1st or 2nd degree. There are a number of issues that arise while creating DCs vaccines that need to be carefully resolved. Among them, the problem of selecting potential targets for the vaccine treatment, the ways to enhance the potency of the vaccine, and the selection of technology for obtaining a sufficient number of functional DCs should be specifically mentioned. The review focuses on the use of autoantigen or alloantibody material for the activation of DCs, and the results of experimental and clinical studies of DCs vaccines in bladder cancer.